Variability of Delivery of Timolol for the Treatment of Infantile Hemangiomas. Issue 4 (29th June 2017) - Yu, JiaDe; Keuter, Tucker; Schilter, Kala; Seefeldt, Marcia; Bates, Brittney; Mueller, Katherine; Drolet, Beth A.
Abstract: Background/Objectives: Topical timolol maleate solution or gel‐forming solution is used alone or in conjunction with oral propranolol for the treatment of infantile hemangiomas. The consistency of the amount of timolol dispensed has never been evaluated. We evaluated the variability of drug delivery between different brands and formulations of timolol solution and gel‐forming solution. Methods: Five blinded volunteers sequentially dispensed five drops from each of the eight bottles containing timolol 0.5% solution or gel‐forming solution. This was repeated three times per user for each bottle. The average amount of timolol dispensed was analyzed according to brand, formulation, and user for variability. The intra‐ and interuser variability of dispensing both formulations of timolol was also measured. Results: Our study demonstrates statistically significant differences in the amount of timolol dispensed between timolol solution and gel‐forming solution, with the latter closer to manufacturer estimates. Significant differences in the amount of timolol dispensed were noted between users regardless of the formulation or brand. Variability in the amount of timolol dispensed was greater for gel‐forming solution than 0.5% solution. Inter‐ and intrauser variability in the amount of timolol dispensed was greater for gel‐forming solution than 0.5% solution. Conclusion: Statistically significant differences were noted in the amount of timolol dispensed according to formulation, brand, and user. Whether this is clinically significant is unknown given the lack of pharmacokinetic data available for timolol.